A European library for Milan: the BEIC Project - Muscogiuri, Marco (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2004)
Milan and the region Lombardy boast a very complex and contradictory reality. There are many public and private libraries. Some of them have a remarkable historical tradition and a considerable ancient and contemporary heritage. However, despite this and all the investments of the last years, the local library services seem to be inadequate compared to the increasing demand coming from the cultural, research and occupational world. Among the interventions carried out in the last years, it is worth mentioning the reopening of the "Biblioteca Ambrosiana", the creation of the "Mediateca" (multimedia library) of Santa Teresa (a branch of the "Biblioteca Braidense"), the reorganization of some peripheral libraries, the gradual computerization of the services, the improved coordination, the investment in new technological and multimedia equipment, the creation of new libraries and the highly dynamic library services of the province. Anyway, Milan is still very far from being able to compete with the other big European capitals in terms of library services. The library infrastructures are still largely undersized with respect to spaces, services provided, promotion and coordination.